Faunal turnover of marine tetrapods during the Jurassic-Cretaceous transition - Benson, Roger B. J.; Druckenmiller, Patrick S. (Biological reviews of the Cambridge Philosophical Society, 2014)
ABSTRACT Marine and terrestrial animals show a mosaic of lineage extinctions and diversifications during the Jurassic–Cretaceous transition. However, despite its potential importance in shaping animal evolution, few palaeontological studies have focussed on this interval and the possible climate and biotic drivers of its faunal turnover. In consequence evolutionary patterns in most groups are poorly understood. We use a new, large morphological dataset to examine patterns of lineage diversity and disparity (variety of form) in the marine tetrapod clade Plesiosauria, and compare these patterns with those of other organisms. Although seven plesiosaurian lineages have been hypothesised as crossing the Jurassic–Cretaceous boundary, our most parsimonious topology suggests the number was only three. The robust recovery of a novel group including most Cretaceous plesiosauroids (Xenopsaria, new clade) is instrumental in this result. Substantial plesiosaurian turnover occurred during the Jurassic–Cretaceous boundary interval, including the loss of substantial pliosaurid, and cryptoclidid diversity and disparity, followed by the radiation of Xenopsaria during the Early Cretaceous. Possible physical drivers of this turnover include climatic fluctuations that influenced oceanic productivity and diversity: Late Jurassic climates were characterised by widespread global monsoonal conditions and increased nutrient flux into the opening Atlantic‐Tethys, resulting in eutrophication and a highly productive, but taxonomically depauperate, plankton. Latest Jurassic and Early Cretaceous climates were more arid, resulting in oligotrophic ocean conditions and high taxonomic diversity of radiolarians, calcareous nannoplankton and possibly ammonoids. However, the observation of discordant extinction patterns in other marine tetrapod groups such as ichthyosaurs and marine crocodylomorphs suggests that clade‐specific factors may have been more important than overarching extrinsic drivers of faunal turnover during the Jurassic–Cretaceous boundary interval.